Feeding the Asian : agricultural R&D and food security - Zhang, Hongzhou. (2012)
Investing in agricultural R&D is certainly critical to safeguarding regional food security, but focusing on small farmers, preserving Asian diet, and cutting food loss and waste are equally, if not more, important.